Serpin-5 regulates prophenoloxidase activation and antimicrobial peptide pathways in the silkworm, Bombyx mori. (June 2016) - Li, Junlan; Ma, Li; Lin, Zhe; Zou, Zhen; Lu, Zhiqiang
Abstract: The prophenoloxidase (PPO) activation pathway and Toll pathway are two critical insect immune responses against microbial infection. Activation of these pathways is mediated by an extracellular serine protease cascade, which is negatively regulated by serpins. In this study, we found that the mRNA abundance of silkworm serpin-5 (BmSpn-5) increased dramatically in the fat body after bacterial infection. The expression level of antimicrobial peptides (AMPs), gloverin-3, cecropin-D and -E decreased in the silkworm larvae injected with recombinant BmSpn-5 protein. Meanwhile, the inhibition of beads melanization, systemic melanization and PPO activation by BmSpn-5 was also observed. By means of immunoaffinity purification and analysis by mass spectrometry, we identified that the silkworm clip domain serine proteases BmHP6 and BmSP21 form a complex with BmSpn-5, which suggests that BmHP6 and SP21 are the cognate proteases of BmSpn-5 and are essential in the serine protease cascade that activates the Toll and PPO pathways. Our study provides a comprehensive characterization of BmSpn-5 and sheds light on the multiple pathways leading to PPO activation and their regulation by serpins. Graphical abstract: Highlights: BmSpn-5 expression is up-regulated in the fat body of silkworm Bombyx mori in response to bacterial infection. BmSpn-5 inhibits beads melanization, systemic melanization and PPO activation in the larval silkworm. BmSpn-5 down-regulates antimicrobial peptides gloverin-3, cecropin-D and -E expression after bacterial infection. BmSpn-5 forms covalent complexes with silkworm clip domain serine proteases BmHP6 and SP21 respectively.